Morphological Influence of Molybdenum Disulfide Nanoparticles on Powder Lubrication and Photocatalysis - Xu, Ze-Yin; Hu, Kun-Hong; Huang, Fei; Han, Cheng-Liang; Hu, Xian-Guo (Asian Journal of Chemistry, 2013)
The lubricating and catalytic properties of two kinds of nano-MoS2, namely nano-sphere and nano-platelet, were investigated. Results showed that the amount of nano-spheres with a low BET area in the contact area was not enough to lubricate the steel friction pair. However, MoS2 nano-platelets with a high BET area could well function as a powder lubricant. The high BET area also improved the catalytic activity of MoS2 nano-platelets. The findings indicated MoS2 nano-platelets have potential applications in powder lubrication and photocatalysis.